2014
DOI: 10.1097/acm.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Publication Productivity, Academic Position, Career Duration, and Funding Among U.S. Academic Radiation Oncology Faculty

Abstract: Purpose There has been much recent interest in promoting gender equality in academic medicine. This study aims to analyze gender differences in rank, career duration, publication productivity and research funding among radiation oncologists at U.S. academic institutions. Methods For 82 domestic academic radiation oncology departments, the authors identified current faculty and recorded their academic rank, degree and gender. The authors recorded bibliographic metrics for physician faculty from a commercially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(160 citation statements)
references
References 28 publications
6
151
2
1
Order By: Relevance
“…Between one-quarter and one-third of women and men (32.4% and 30.2% for parents, 22.5% and 29.6% for nonparents, and 26.5% and 29.9% for all respondents, respectively) reported they were "very likely" to pursue a career in academics ( Table 2). This is especially encouraging, given recent reports describing gender disparities in academic productivity and career trajectory in academic medicine more broadly (11) as well as in the field of radiation oncology (17). One recent study of radiation oncology residents and recent graduates reported that female trainees were less academically productive when it came to publications; but after stratifying for career aspiration (academic vs private practice), the gender differences were no longer significant (18).…”
Section: Gender Differences In Academic Productivity and Career Aspirmentioning
confidence: 59%
“…Between one-quarter and one-third of women and men (32.4% and 30.2% for parents, 22.5% and 29.6% for nonparents, and 26.5% and 29.9% for all respondents, respectively) reported they were "very likely" to pursue a career in academics ( Table 2). This is especially encouraging, given recent reports describing gender disparities in academic productivity and career trajectory in academic medicine more broadly (11) as well as in the field of radiation oncology (17). One recent study of radiation oncology residents and recent graduates reported that female trainees were less academically productive when it came to publications; but after stratifying for career aspiration (academic vs private practice), the gender differences were no longer significant (18).…”
Section: Gender Differences In Academic Productivity and Career Aspirmentioning
confidence: 59%
“…Other investigators have previously used this measure to compare scholarly activity among faculty of various medical specialties in the United States. [5][6][7][8][9] One prior study in academic radiology, for example, identified a threshold h-index of 15 as the breakpoint between junior and senior faculty, 5 and another study, also of academic radiologists, identified a threshold h-index of 10 as predictive of securing National Institutes of Health funding among academic radiologists. 8 We decided to use SCOPUS as our primary database given its calculation of the h-index as well as its comprehensive inclusion of citations from published manuscripts and exclusion of abstracts and unpublished works.…”
Section: Bibliometric Measures Of Research Productivity: H-index and mentioning
confidence: 98%
“…A number of explanations have been advanced to explain sex differences in faculty rank, [7][8][9][20][21][22][23][24] including explanations for why women faculty have lower average research productivity than men, 24 which may impede promotion, and explanations for why, even after accounting for research productivity, women are less likely than men to be full professors. 9 Differential household responsibilities, 22,25,26 childrearing, and different preferences on work-life balance 27,28 may contribute to sex differences in full professorship primarily by reducing research productivity but should have little independent effect on faculty rank once measures of productivity are accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…Potential interventions to address these barriers to promotion include greater investment in early research career development for women and modifying the promotions process in nonresearch career tracks. Alleviating sex differences in promotion from associate to full professor may require a distinct set of strategies.A number of explanations have been advanced to explain sex differences in faculty rank, [7][8][9][20][21][22][23][24] including explanations for why women faculty have lower average research productivity than men, 24 which may impede promotion, and explanations for why, even after accounting for research productivity, women are less likely than men to be full 22,25,26 childrearing, and different preferences on work-life balance 27,28 may contribute to sex differences in full professorship primarily by reducing research productivity but should have little independent effect on faculty rank once measures of productivity are accounted for. In contrast, women may face difficulties finding effective mentors and receiving recognition from senior colleagues, 7,20,21,29 workplace discrimination, and inequitable allocation of institutional resources.…”
mentioning
confidence: 99%